Precarious Work? Migrants’ Narratives of Coping with Working Conditions in the Danish Labour Market - Pljevaljcic-Simkunas, Doris; Thomsen, T L (Central and Eastern European Migration Review, 2018)
This article deals with migrants’ experiences of precarious working conditions in the cleaning and construction industries in the Danish labour market as seen from their perspective. The experiences are retained through biographical narrative interviews with migrant workers from Central and Eastern Europe and are used to gain an understanding of the concrete strategies they apply when coping with their short-term contracts, demanding working hours, risk of unemployment and other insecurities. Migrants’ experiences of precarity and insecurity in their work is confirmed, to some degree, in numerous research studies. However, the resistance and strategies expressed by the migrant workers in their narratives show that they have also developed specific ways to cope with this precarity. The article contributes to a new understanding of migrants’ responses to precarity in which they engage their social and cultural resources to cope with the labour market conditions they face in Denmark.
Keywords: biographical narratives; cultural and social capital; labour security; migrant workers; precarious working conditions